2023
DOI: 10.1007/s00221-023-06617-6
|View full text |Cite
|
Sign up to set email alerts
|

How the timing of visual feedback influences goal-directed arm movements: delays and presentation rates

Abstract: Visual feedback normally helps guide movements to their goal. When moving one’s hand, such guidance has to deal with a sensorimotor delay of about 100 ms. When moving a cursor, it also has to deal with a delay of tens of milliseconds that arises between the hand moving the mouse and the cursor moving on the screen. Moreover, the cursor is presented at a certain rate, so only positions corresponding with the position of the mouse at certain moments are presented. How does the additional delay and the rate at wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Visual feedback latencies are an inherent component of human-computer interactions that rely on continuous task feedback, from everyday computer mouse use 1 to sophisticated virtual and augmented reality systems used for skill training in tasks like the operation of surgical robotic systems 2,3 , rehabilitation 4 , and flight simulators 5 . While these latencies due to delayed system response times are commonly short (<100ms) -a level at which they are often not perceived 6 research has shown that even sub-100ms feedback latencies can markedly reduce motor performance in tasks such as reaching, tracking, steering, and collaborative control [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual feedback latencies are an inherent component of human-computer interactions that rely on continuous task feedback, from everyday computer mouse use 1 to sophisticated virtual and augmented reality systems used for skill training in tasks like the operation of surgical robotic systems 2,3 , rehabilitation 4 , and flight simulators 5 . While these latencies due to delayed system response times are commonly short (<100ms) -a level at which they are often not perceived 6 research has shown that even sub-100ms feedback latencies can markedly reduce motor performance in tasks such as reaching, tracking, steering, and collaborative control [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18].5° for explicit generalization. Moreover, we found that, like implicit adaptation during the training and retraining periods, the local component of implicit generalization grew as latency decreased (5.6±0.9° vs 7.7±0.7° for 85ms vs. 25ms, t(66)=1.8, p= 0.042; and 5.5±1.0° vs 7.7±0.7° for 300ms vs. 25ms, t(66)=1.7, p= 0.043).…”
mentioning
confidence: 99%